Peran Zakat dalam Menumbuhkan Kesejahteraan Masyarakat - Maula Nasrifah (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2020)
Zakat is a responsibility for Muslims. Zakat can cleanse of the soul and give a big income for Muslims community's economyc strenght. So it can be said that zakat is the main indicator for community welfare in poverty alleviation. The Purpose of this study to explain the role of zakat to grow community welfare by using the case study BAZNAS East Java and providing an explanation of the Welfare Index for BAZNAS East Java. This study uses a quantitative approach. Data obtained through questionnaires and measured using the Welfare Index for BAZNAS to see the impact of zakat distribution conducted by BAZNAS East Java to their mustahiq. The results of this study explained that zakat has a big role in fostering this social welfare as evidenced by the very IKB 2018 value which is 0.95 and has increased significantly compared to the previous year.